AN ANALYSIS OF SOCIOECONOMIC INEQUALITIES AMONG LOW-INCOME INDIVIDUALS WITH A SPECIFIC FOCUS ON THE COMPLIANCE INDEX OF SHARIAH GENERAL BANKS IN INDONESIA - Shah Zada, T. Muhammad; Nasirwan, Nasirwan; Zainal, Andri (Universitas Negeri Medan, 2024)
The aim of this study is to investigate the correlation between the focus on the overall compliance index of sharia banks in Indonesia, particularly the profitability role index, sharia supervisory boards, and independent commissioners, and reducing social disparity among low-income groups. This study specifically examines the sharia commercial banks in Indonesia, and the samples were chosen using the purposive sampling method. The data collected comprises secondary data, specifically the annual reports of sharia commercial banks from 2017 to 2021. The data underwent the usual assumption test for analysis. Applying the multiple linear regression method for hypothesis testing. The SPSS software is employed for data processing. The results of this study suggest that the presence of an audit committee has a significant and positive effect on the sharia compliance index. The variables of liquidity, profitability, leverage, and sharia supervisory board have a negative and statistically insignificant effect on the sharia compliance index. The independent commissioner variable has a favourable effect on the sharia compliance index, although this effect is statistically insignificant. Therefore, it may be inferred that the profitability index, Sharia Supervisory Board, and Independent Commissioners, which serve as benchmarks for guaranteeing Sharia compliance in Indonesian Sharia banks, are not successful in alleviating the prevailing social inequality in Indonesia.